The causal effect of income on market social responsibility - Björn Bartling; Vanessa Valero; Roberto A. Weber (University of Zurich, Department of Economics, 2024)
We investigate the relationship between consumers' income and socially responsible consumption that mitigates negative externalities. We conduct laboratory and online market experiments in which firms and consumers can exchange products that differ in the degree to which they diminish negative external impacts at the expense of higher production costs. Our treatments exogenously vary consumers' income. Across all three experiments, higher income causes an increase in the quantity of socially responsible products purchased and at least slightly increases the share of such products as part of total consumption. However, increases in total consumption resulting from higher income can increase negative externalities.
Keywords: C92; D31; D62; M14; 330; Negative externalities; social and environmental responsibility; income effects; market experiments